2022
DOI: 10.3390/ma15134475
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength and Chloride Ions’ Penetration of Alkali-Activated Concretes (AAC) with Blended Precursor

Abstract: The purpose of this study was to investigate the properties of hardened alkali-activated concrete, which is considered an eco-friendly alternative to Portland cement concrete. In this paper, the precursors for alkali-activated concrete preparations are blends of fly ash and ground-granulated blast-furnace slag in three slag proportions: 5%, 20%, and 35%, expressed as a percentage of fly ash mass. Thus, three concretes were designed and cast, denominated as AAC5, AAC20, and AAC35. Their physical and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…An important influence of the ground granulated blast-furnace slag on the compressive strength and chloride penetration resistance has been reported by Du ży et al [44]. This can partly be explained by the fact that there was a possible total porosity and effective porosity reduction due to the GGBFS addition.…”
Section: Non-steady-state Chloride Migration Coefficient Of Concretementioning
confidence: 87%
“…An important influence of the ground granulated blast-furnace slag on the compressive strength and chloride penetration resistance has been reported by Du ży et al [44]. This can partly be explained by the fact that there was a possible total porosity and effective porosity reduction due to the GGBFS addition.…”
Section: Non-steady-state Chloride Migration Coefficient Of Concretementioning
confidence: 87%
“…GGBFS [17,23,[27][28][29]33,35,41,42,45,46,48,49,[51][52][53][54][55][56]59,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] Ground granulated blast furnace slag (GGBFS) is a by-product of the iron-making process.…”
Section: It Was Used As a Precursormentioning
confidence: 99%
“…One of the studies explored sodium-carbonate-activated slag glass powder [82]. It was also used as a single source for precursor and as part of binary and ternary blended precursors with a variety of conventional and/or alternative feedstocks [17,[27][28][29]33,35,41,42,45,46,49,[51][52][53][54][55][56]59,67,69,70,72,73,75,76,78,81,83,84]. Additionally, mixed precursors containing different ratios of rice husk (RH), RHA, MK, palm oil fuel ash (POFA), and GGBFS were investigated [79].…”
Section: It Was Used As a Precursormentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many research reports on this kind of material, and some have demonstrated sufficient mechanical properties for structural materials [ 3 , 4 ]. It is also believed that they have higher durability against salt penetration and chemical attacks than conventional cement concrete [ 5 , 6 , 7 ]. Fundamental research on the durability of alkali-activated materials in a sewer environment was also reported [ 8 ].…”
Section: Introductionmentioning
confidence: 99%